The Effect of Green Accounting Implementation, Environmental Performance, and Company Size on the Finance Perfomance of Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2022-2024 - Muhammad Riyan Fahlefi; Rita Friyani; Riski Hernando (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to examine the influence of the implementation of green accounting, environmental performance, and company size on financial performance in energy sector companies listed on the Bursa Efek Indonesia during the period 2022-2024. Sampling was conducted using purposive sampling with a sample size of 19 from a total population of 83 companies. The study period of 3 years produced 57 panel data. Data analysis was performed using SPSS version 29 software. The results show that the implementation of green accounting has no effect on financial performance, environmental performance has a negative effect, while company size has a positive effect on financial performance.